Is ionized oxygen negatively or positively charged more effective for carboxyhemoglobin reduction compare to medical oxygen at atmospheric pressure? - Perečinský, S; Kron, I; Engler, I; Murínová, L; Donič, V; Varga, M; Marossy, A; Legáth, Ľ (Physiological research, 2015)
Carbon monoxide (CO) reversibly binds to hemoglobin forming carboxyhemoglobin (COHb). CO competes with O(2) for binding place in hemoglobin leading to tissue hypoxia. Already 30 % saturation of COHb can be deadly. Medical oxygen at atmospheric pressure as a therapy is not enough effective. Therefore hyperbaric oxygen O(2) inhalation is recommended. There was a question if partially ionized oxygen can be a better treatment at atmospheric pressure. In present study we evaluated effect of partially ionized oxygen produced by device Oxygen Ion 3000 by Dr. Engler in elimination of COHb in vitro experiments and in smokers. Diluted blood with different content of CO was purged with 5 l/min of either medicinal oxygen O(2), negatively ionized O(2) or positively ionized O(2) for 15 min, then the COHb content was checked. In vivo study, 15 smokers inhaled of either medicinal oxygen O(2) or negatively ionized O(2), than we compared CO levels in expired air before and after inhalation. In both studies we found the highest elimination of CO when we used negatively ionized O(2). These results confirmed the benefit of short inhalation of negatively ionized O(2), in frame of Ionized Oxygen Therapy (I O(2)Th/Engler) which could be used in smokers for decreasing of COHb in blood.
Keywords: otrava oxidem uhelnatým; Carbon Monoxide Poisoning; Oxygen; kyslík; Humans; ionty; lidé; Ions